Montelukast as Add-On Therapy with Inhaled Corticosteroids or Inhaled Corticosteroids and Long-Acting Beta-2-Agonists in the Management of Patients Diagnosed with Asthma and Concurrent Allergic Rhinitis (The RADAR Trial) - Paul K Keith; Caroline Koch; Michel Djandji; Jacques Bouchard; Eliofotisti Psaradellis; John S Sampalis; R Robert Schellenberg; R Andrew McIvor (Canadian Respiratory Journal)
OBJECTIVE: To evaluate the effectiveness of montelukast as add-on therapy for patients diagnosed with asthma and concurrent allergic rhinitis who remain uncontrolled while receiving inhaled corticosteroid (ICS) monotherapy or ICS/long-acting beta-2-agonist (LABA) therapy in a community practice setting.